PRODUCT INNOVATION OF SHARIA FINANCIAL INSTITUTION: THEORY REVIEW - Mulyadi, Dedi; Athoillah, Mohamad Anton (Journal of Economicate Studies, 2017)
Competitions in the financial industry are so tight that sharia banks can no longer simply rely on standard products to attract the public. The development of sharia banking products and services should not merely 'imitate' from conventional banking products. However, the development of this innovation product does not mean eliminating the principles of syariah let alone just be used as legal and administrative hilah to gain profit alone, on the grounds that Islamic banks are positioned as a financial intermediary institution based on business not a social institution. Based on these problems, the authors get some solution that is, development of innovation (product) is permitted when there is a stronger proposition and clarity of meaning contained therein, conformity with the purpose of sharia (maqashid al-syariah), and relevance to the development of the times and needs Human beings will transactions and modern contracts.